If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) = -5(6 + -1x) Reorder the terms: 3(-4 + x) = -5(6 + -1x) (-4 * 3 + x * 3) = -5(6 + -1x) (-12 + 3x) = -5(6 + -1x) -12 + 3x = (6 * -5 + -1x * -5) -12 + 3x = (-30 + 5x) Solving -12 + 3x = -30 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -12 + 3x + -5x = -30 + 5x + -5x Combine like terms: 3x + -5x = -2x -12 + -2x = -30 + 5x + -5x Combine like terms: 5x + -5x = 0 -12 + -2x = -30 + 0 -12 + -2x = -30 Add '12' to each side of the equation. -12 + 12 + -2x = -30 + 12 Combine like terms: -12 + 12 = 0 0 + -2x = -30 + 12 -2x = -30 + 12 Combine like terms: -30 + 12 = -18 -2x = -18 Divide each side by '-2'. x = 9 Simplifying x = 9
| 2x^4-14x^3+12x^2-15=0 | | 15+2p=17 | | -x^7+5x^2-2x^2= | | 2/7(21y+14)-2(4y+6)=0 | | 5x-3=7x+3x | | -24+-24=42 | | 3x+15x-15=-3 | | 9(m-[-5])=108 | | y=3mx-5b | | -6(0.1x+0.2)-2.2=0.4 | | 2/3(1/4-X)=5/7(3-1/4X) | | x^2-17x+12=0 | | 8m+3=-13 | | -7-y-y=1 | | 5x^2-85=0 | | 6p^2-7p+2=0 | | 1.12/0.8 | | 3(x-2)=5(x+1)-17 | | 5y+4=2y-6 | | .5+3r=5r-19 | | 10^2/5^2+(6^3/4)^2/9+60^1/8.3^0-2(2^5-3^3) | | c^2-9c-8=0 | | 5y-10-2y=5 | | 9.75x+1.25=4.25 | | x-1-2x=3x+5 | | (7v^2-5v-4)+(6v^2-3v+2)= | | 21x+63=-x+3 | | 28-7=14 | | sec^2x-4=0 | | -3x+3(-6)=-6 | | 28-7= | | 7-5t=12t |